2011
DOI: 10.15560/7.5.574
|View full text |Cite
|
Sign up to set email alerts
|

Amphibia, Anura, Hylidae, Scarthyla vigilans (Solano, 1971): range extension and new country record for Trinidad, West Indies, with notes on tadpoles, habitat, behavior and biogeographical significance

Abstract: We report a range extension and new country record for Scarthyla vigilans in Trinidad, West Indies. The species was previously known only from populations on mainland South America. We include notes on behavior, habitat and tadpole development, and discuss the biogeographical significance of the species’ presence in Trinidad, particularly with respect to consequences for understanding colonization events on this Caribbean island.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Lineage 8 corresponds to D. stingi and its original description does not provide a comparison with D. amicorum (see Kaplan, 1994). Lineages 1 to 6 are distributed over the Guiana Shield, and Gehara et al (2014) suggested that they might correspond to D. goughi , at the time a synonym of D. minutus based on specimens from Trinidad—a reasonable suggestion given that many species from Trinidad are also found in the lowlands of Venezuela and Colombia (Kenny, 1969; Suarez‐Mayorga and Lynch, 2001a; Suarez‐Mayorga and Lynch, 2001b; Barrio‐Amoros et al, 2006; Camargo et al, 2006; Smith et al, 2011). Recently, Barrio‐Amorós et al, (2019) re‐examined the holotype of Dendropsophus goughi and came to the conclusion that it should be considered a junior synonym of D. microcephalus .…”
Section: Discussionmentioning
confidence: 99%
“…Lineage 8 corresponds to D. stingi and its original description does not provide a comparison with D. amicorum (see Kaplan, 1994). Lineages 1 to 6 are distributed over the Guiana Shield, and Gehara et al (2014) suggested that they might correspond to D. goughi , at the time a synonym of D. minutus based on specimens from Trinidad—a reasonable suggestion given that many species from Trinidad are also found in the lowlands of Venezuela and Colombia (Kenny, 1969; Suarez‐Mayorga and Lynch, 2001a; Suarez‐Mayorga and Lynch, 2001b; Barrio‐Amoros et al, 2006; Camargo et al, 2006; Smith et al, 2011). Recently, Barrio‐Amorós et al, (2019) re‐examined the holotype of Dendropsophus goughi and came to the conclusion that it should be considered a junior synonym of D. microcephalus .…”
Section: Discussionmentioning
confidence: 99%